2008
DOI: 10.1016/j.virol.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in simian immunodeficiency virus reverse transcriptase alleles that appear during infection of macaques enhance infectivity and replication in CD4+ T cells

Abstract: We previously showed that a slowly replicating, minimally pathogenic clone of simian immunodeficiency virus (SIV), SIVmneCl8, evolves increased ability to replicate in T cells with the onset of AIDS in pig-tailed macaques. Moreover, molecular clones derived from late stages of infection (SIVmne170 and SIVmne027) replicate to high levels in vivo compared to SIVmneCl8. Here, we investigated the role of rt mutations in SIVmne variant replication. We demonstrate selection for rt alleles that enhance viral infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…PBMC were isolated from heparinized rhesus, pig-tail, or human peripheral blood by Ficoll gradient centrifugation and activated by costimulation with anti-CD3/anti-CD28 monoclonal antibodies and interleukin-2 as previously described (7,9,46). At 3 days after costimulation the cells were Ͼ98% CD3 ϩ T cells, as indicated by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…PBMC were isolated from heparinized rhesus, pig-tail, or human peripheral blood by Ficoll gradient centrifugation and activated by costimulation with anti-CD3/anti-CD28 monoclonal antibodies and interleukin-2 as previously described (7,9,46). At 3 days after costimulation the cells were Ͼ98% CD3 ϩ T cells, as indicated by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…macrophages, resting T cells, activated T cells) have variable dNTP pools (Traut, 1994;Diamond et al 2004;Hauschka, 1973;Fuller et al 1982;Skoog and Bjursell, 1974;Yao et al 2003). A recent study with SIV RT variants isolated from infected macaques demonstrated rapid selection against an RT variant with higher replication fi delity (Biesinger et al 2008). These data suggest that RT's ability to misincorporate dNTPs in settings with limited resource availability or the indirect effect misincorporation has on processivity allows for more rapid genomic reverse transcription and integration and is an important aspect of replication fi tness.…”
Section: Viral Determinants Altering Phenotypementioning
confidence: 99%
“…9 Indeed, our studies with the SIV-macaque model demonstrated that the appearance of variants with greater replicative capacity in CD4+ T-cells influenced plasma viral load and the rate of disease progression. 29 Importantly, highly pathogenic variants also show greater replicative capacity in DC-T-cell cocultures compared to the minimally pathogenic parental virus 26, 30 , suggesting that SIV, and by extension HIV-1, evolve during infection to exploit DC-T-cell interactions for viral replication. The data presented here support this hypothesis and show a direct relationship between plasma viral RNA levels in the host and infectivity and replication capacity of the infecting viruses in DC-T-cell cocultures.…”
Section: Discussionmentioning
confidence: 99%